Perspektif Multidimensional Pendidikan Pembangunan Berkelanjutan: Pemikiran Awal Konsep dan Penerapan - Iskandar Agung (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
Development is a term expressed by all parties to promote the effort to create changes in the public toward a better life. Implementation of the Development is often performed multidimensionally in which most of the aspects in life (such as economy, social, education, politic, health, etc) are covered therein. Even though all of the Developments are aimed to improve, advance and achieve the welfare ofÂ the target society but in reality it is often found that a success in a Development is not followed by proper care and maintenance, worst of all, it is even threatened or vandalized by some of the irresponsible and reckless members of the society. In addition, it must be admitted that not all Developments can give positive impact to the society, some of which even create negative impacts against their life. On the basis of the premises mentioned above, it is necessary to introduce the concept of Sustainable Development so as to make sure that the Development will be properly cared-for, maintained, and even continued to the next level for the sake of the present and the future generations. One of the potential elements which can be used for implanting the values and objectives of the Development into the heart and mind of the society is Education, which is known as Education Sustainable Development. However, there has been no clear conception yet about the Education Sustainable Development which can be used as the guidelines and references at operational level by relevant parties. Therefore, this writing is intended to offer a concept of Education Sustainable Development, and the method for promoting the values and objectives of the Development through Education, especially are integrated into the intra and extracurricular activities.Â ABSTRAKPembangunan merupakan istilah yang dikemukakan oleh berbagai pihak sebagai upaya mencapai perubahan masyarakat ke arah kehidupan yang lebih baik. Pembangunan kerapkali dilaksanakan secara multidimensional, dalam arti meliputi berbagai dimensi kehidupan (ekonomi, sosial, pendidikan, politik, kesehatan, dan sebagainya), meski keseluruhan bermuara pada upaya menuju perbaikkan, kemajuan dan kesejahteraan hidup masyarakat penerimanya. Namun tidak jarang fenomena di sekitar memperlihatkan, keberhasilan suatu pembangunan kurang dapat dipertahankan, terancam kesinambungannya, dan bahkan dirusak oleh sebagian anggota masyarakat penerimanya. Di samping itu, pembangunan yag dilaksanakan pun tidak hanya membawa dampak positif, tetapi juga negatif dalam kehidupan masyarakat. Atas dasar itu diperkenalkan konsepsi pembangunan berkelanjutan (sustainable development) dengan tujuan agar pembangunan dapat dijaga, dipelihara, dan bahkan dikembangkan keberlanjutannya untuk kepentingan generasi masa kini maupun akan datang. Salah satu unsur potensial untuk menanamkan nilai dan tujuan pembangunan itu adalah melalui bidang pendidikan, yang dikenal dengan sebutan pendidikan pembangunan berkelanjutan (education sustainable development). Belum terdapat kejelasan konsepsional mengenai istilah pendidikan pembangunan berkelanjutan tersebut yang dapat digunakan sebagai pedoman atau acuan operasionalisasinya oleh berbagai pihak di lapangan. Atas dasar itu tulisan ini bermaksud mengemukakan suatu pemikiran mengenai pengertian pembangunan berkelanjutan serta cara untuk menyebarluaskan nilai dan tujuan yang terkandung dalam dimensi pembangunan melalui jalur pendidikan, terutama mengintegrasikannya ke dalam kegiatan intra dan ekstrakurikuler.